Optimizing the Role of Information and Communications Technology within the State Administrative Court Environment - Nasrullah; Handayani, I Gusti Ayu Ketut Rachmi; Karjoko, Lego; Susilo, Agus Budi; Qazi Zada, Mohd Ziaolhaq (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2000)
With an increasingly complex judicial landscape, Information and Communications Technology (hereinafter referred to as ICT) has become the key factor in improving the efficiency, transparency, and accessibility of the modern justice system. This article explores the crucial role of ICT in changing judicial governance, especially within the State Administrative Court (PTUN). This article also identifies the challenges faced in the implementation of ICT. It initiates efforts to optimize the role of ICT in overcoming technical obstacles and realizing justice in the PTUN environment. The method used was doctrinal legal research using secondary data through statute and analytical approaches. The collected data were analyzed in a descriptive, prescriptive, and qualitative manner. The results illustrated that ICT significantly improved the performance, transparency, efficiency, and accessibility of the state administrative court's judicial system. Optimizing and expanding the reach of ICT utilization, especially in overcoming obstacles to executing PTUN decisions that have permanent legal force (inkracht van bewijsde), is an essential challenge and need for PTUN that continues to adapt to technological developments to ensure the continuity of judicial transformation, especially within the PTUN.